2002
DOI: 10.1021/es020554x
|View full text |Cite
|
Sign up to set email alerts
|

Demonstration of the “Conditioning Effect” in Soil Organic Matter in Support of a Pore Deformation Mechanism for Sorption Hysteresis

Abstract: Hysteresis, or isotherm nonsingularity, is a confounding issue in sorption research that undermines the commonplace assumption of reversibility in environmental fate and effects models for organic compounds in soil media. Until now, a molecular-level mechanism for true hysteresis when the sorbate is retrievable, structurally intact, has not been forthcoming. We show here that two organic soils exhibit the "conditioning effect", which refers to the enhancement in sorption of a compound following brief exposure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
140
0
3

Year Published

2005
2005
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 176 publications
(153 citation statements)
references
References 23 publications
(29 reference statements)
10
140
0
3
Order By: Relevance
“…In the case of swelling, for example, the total sorption capacity on the desorption path may be larger than the initial sorption capacity. Another mechanism is the so-called conditioning effect, which manifests itself in the fact that subsequent (ad)sorption measurements on the same material tend to give higher sorption uptake (Lu and Pignatello, 2002;Wang et al, 1998). For the CFCMS sample we have found that after we had performed two adsorption runs described above (Fig.…”
Section: Discussionmentioning
confidence: 93%
“…In the case of swelling, for example, the total sorption capacity on the desorption path may be larger than the initial sorption capacity. Another mechanism is the so-called conditioning effect, which manifests itself in the fact that subsequent (ad)sorption measurements on the same material tend to give higher sorption uptake (Lu and Pignatello, 2002;Wang et al, 1998). For the CFCMS sample we have found that after we had performed two adsorption runs described above (Fig.…”
Section: Discussionmentioning
confidence: 93%
“…The dual-mode model by Vrentas and Vrentas [79] could perhaps solve the problem, as it considers that the phenomenon of hysteresis occurs because the material is in two different physical states in the adsorption and desorption processes [80,81]. Hill et al [82] assumed that thermodynamic equilibrium was reached locally in each process.…”
Section: Discussionmentioning
confidence: 99%
“…During desorption, relaxation of the matrix to the state it was in during adsorption is kinetically hindered. 54 The free volume (that is internal cell wall space not occupied by macromolecules; also termed microcapillaries) is greater on desorption compared to adsorption, hence adsorption and desorption are occurring within different physical environments. 55 The effect of matrix crosslinking upon hysteresis was tested using humic soils treated with Al 3þ ions, where it was found that increased hysteresis was linked to a higher crosslinking density.…”
Section: Comparison Of Different Fibersmentioning
confidence: 99%